The use of thromboelastography and the functional tests with double local hypoxia of the upper limb to assess the risk of thromboembolism in patients undergoing surgery - Tarabrin, O.; Gozhenko, A.; Vorotyntsev, S.; Kobelyatsky, Y.; Volkova, Y.; Nesterenko, O.; Snisar, V.; Sorokina, O.; Cherniy, V.; Dudukina, S.; Surkov, D.; Kirpichnikova, K.; et al. (Journal of Education, Health and Sport, 2023)
Introduction: Prothrombotic is considered a condition that leads to the development of venous or arterial thrombosis and its consequences. There are many factors that cause a violation of the hemostatic potential in patients undergoing surgery with existing risk factors for thromboembolism, a more detailed study of the blood coagulation system, including the study of the compensatory capabilities of the hemocoagulation system, should be conducted. One of these methods is a functional test with double local hypoxia of the upper limb (DLHUL) under the control of thromboelastography (TEG). Goals: The purpose of the study - to identify the degree of thrombotic risk in patients preparing for planned surgical intervention, who belong to the risk group of thrombotic complications, to compare and evaluate the state of the hemostasis system in healthy volunteers and in this cohort of patients using a functional test with double local hypoxia of the upper limb by the method of thromboelastography. Materials and methods: A randomized prospective study was conducted. Patients were divided into two groups depending on the presence of risk factors for thrombosis. Group 1 consisted of healthy volunteers (n = 40) who are not at risk of thrombosis. Group 2 includes patients with existing factors of thrombotic risk (n = 120) who are preparing for scheduled surgical interventions. These patients underwent a functional test of "double local hypoxia of the upper limb" (DLHUL) using thromboelastographic (TEG) methods of studying the hemocoagulation system. The main task of this functional test is to create a trigger component to determine the limits of hemostasis, the origin and duration of adaptive and compensatory reactions of the hemostasis system. Indicators of the hemostasis system are recorded using a thromboelastograph before and after the test. The links of hemostasis are reflected by the following indicators: aggregate state of blood (A0), contact coagulation intensity (CCI), coagulation drive intensity (ICD), maximum clot density - maximum activity (MA), fibrinolytic activity - clot retraction and lysis index (IRCL). The results. Analyzing the data of thromboelastography after performing DLHUL, among the patients of Group 1, two types of reaction of the hemostasis system were found in patients without predictors of thrombotic risk: compensated (n= 20) (characterized by a decrease in the indicators of the vascular-platelet component; subcompensated (n = 20) (characterized by an increase in the indicators of the vascular -platelet component). In subjects of Group 1, TEG indicators indicate an increase in the external mechanism of prothrombinase formation, and the reaction of the procoagulant link of the blood coagulation system in response to the influence of a trigger indicates a change in the directionality of the hemostatic potential towards hypercoagulation. In subjects of group 1 with a compensated type, there is an increase in the components of fibrinolysis and a deviation of the hemostatic potential towards hypocoagulation is observed. The state of the hemostasis system in patients of Group 2 is characterized by pronounced changes in the hemostatic potential in all links. In the vascular-platelet link, a violation of platelet aggregation was noted, with an increase in indicators in response to a stimulus. When conducting the DLHUL test in the subjects of group 2, a decompensated (n = 98) and exhausted (n = 22) type of reaction to the test with local hypoxia of the upper limb was determined. That is, with increased platelet aggregation, hypercoagulation, inhibition of the anticoagulant system and fibrinolysis before the action of the trigger factor, after performing the DLHUL test, these disorders in the hemostasis system progress towards hypercoagulation, which is indicated by the increase in platelet aggregation, the strengthening of the coagulation link of the hemostatic system, the depression of fibrinolysis increases . However, the intensity of these changes is not as high as in patients of group 1 after the DLHUL test. Conclusions: The test with double local hypoxia of the upper limb is effective as a trigger factor to determine the compensatory capabilities of the HS. Depending on the type of reaction of the platelet-vascular, coagulation components of hemostasis and fibrinolysis to the influence of the trigger, two types of reaction of the blood aggregate state regulation system are possible in people who do not have an anamnesis of factors provoking a hypercoagulable state: compensated and subcompensated. Therefore, when planning surgical intervention in this cohort of patients, the risk of thrombotic complications is low. Depending on the type of reaction of the platelet-vascular, coagulation components of hemostasis and fibrinolysis to the influence of the trigger, two types of reaction of the blood aggregate state regulation system are possible in people with an anamnesis of factors provoking a hypercoagulable state: decompensated (more often) and depleted (less often). Patients with a history of factors provoking a hypercoagulable state have a high risk of perioperative thrombotic complications and a possible risk of thrombo-hemorrhagic complications, including the syndrome of disseminated intravascular coagulation. Changes in all links of the hemostasis system in response to the DLHUL test indicate the need to use anticoagulant therapy in patients with an anamnesis of factors provoking a hypercoagulable state as one of the components of preoperative preparation.